(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present paper tests into the concept of adoration uncovered in the Dark Lady bunch in Shakespeare’s Sonnets. In these poems, the artist portrays a sort of fixation, unpleasant, sad and deteriorating, which is entirely unexpected from that sweet and praising affection Shakespeare consistently seeks after in his initial works. It is contended that the contention between the perfect of affection and the sexy fixation on the Dark Lady likely could be a sign of the adjustment in the artist’s temperament, to be specific, from positive thinking to cynicism.